"Semicut” skill on the cystic duct in laparoscopic cholecystectomy - Liu, Linxun; Zhao, Zhanxue; Yang, Jinyu (Frontiers in Surgery, 2023)
This study aimed to decrease the incidence of residual stones in the cystic duct and consequently decrease the incidences of intractable pain and the formation of a small gallbladder after laparoscopic cholecystectomy (LC). We changed the order of the clamps when performing LC, used the “semicut” skill of the cystic duct, and removed the stones residing in the cystic duct. A total of 45 patients underwent the operation, and all operations were completed successfully. This technique did not increase the operation time or difficulty. In conclusion, the “semicut” skill of the cystic duct is a safe and feasible surgical method that may change the occurrence of intractable pain after LC.